1998
DOI: 10.1002/(sici)1097-0142(19980115)82:2<403::aid-cncr21>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Dietary omega-3 polyunsaturated fatty acids plus vitamin E restore immunodeficiency and prolong survival for severely ill patients with generalized malignancy

Abstract: Malnutrition appears to be an important predictor of survival for patients with end stage malignant disease. Omega-3 polyunsaturated fatty acids had a significant immunomodulating effect and seemed to prolong the survival of malnourished patients with generalized malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
186
0
11

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(199 citation statements)
references
References 22 publications
2
186
0
11
Order By: Relevance
“…The vast majority of the clinical trials in which fish oil derived n-3 PUFAs were tested report an increase (Wigmore et al, 1996(Wigmore et al, , 2000Barber et al, 1999Barber et al, , 2001Jatoi et al, 2004) or maintenance (Burns et al, 1999(Burns et al, , 2004Fearon et al, 2003) of body weight (BW), whereas in two other clinical trials no effect on the loss of BW was found (Gogos et al, 1998;Bruera et al, 2003). In the latter, however, the supplementation period was only 2 weeks (Bruera et al, 2003) and/or only a small number of patients was included (Gogos et al, 1998). In a clinical trial in pancreatic cancer patients, in which a fish oil-enriched product was tested against an isocaloric/isonitrogenous placebo, no differences between groups were found on either LBM or physical activity.…”
mentioning
confidence: 99%
“…The vast majority of the clinical trials in which fish oil derived n-3 PUFAs were tested report an increase (Wigmore et al, 1996(Wigmore et al, , 2000Barber et al, 1999Barber et al, , 2001Jatoi et al, 2004) or maintenance (Burns et al, 1999(Burns et al, , 2004Fearon et al, 2003) of body weight (BW), whereas in two other clinical trials no effect on the loss of BW was found (Gogos et al, 1998;Bruera et al, 2003). In the latter, however, the supplementation period was only 2 weeks (Bruera et al, 2003) and/or only a small number of patients was included (Gogos et al, 1998). In a clinical trial in pancreatic cancer patients, in which a fish oil-enriched product was tested against an isocaloric/isonitrogenous placebo, no differences between groups were found on either LBM or physical activity.…”
mentioning
confidence: 99%
“…The efficacy of fatty acid incorporation during our short-term fish oil supplementation may be compared with related studies. Other authors employing fish oil capsules (Barber et al, 1998;Gogos et al, 1998) or fish oilenriched enteral formula (Barber, 2001) to deliver similar amounts of fish oil to those reported here, report comparable elevations of per cent n-3 fatty acids in plasma PL of advanced cancer patients using longer intervention periods (Wigmore et al, 1997;Barber et al, 1999). In the present study, the ratio of 20 : 3 n-9 to 20 : 4 n-6 in plasma PL was reduced following the fish oil treatment and may suggest an improvement in essential fatty acid status.…”
Section: Discussionmentioning
confidence: 99%
“…Gogos et al (1998) have failed to find effects of supplementation of 5 . 1 g EPA + DHA/d for 6 weeks on serum TNFa, IL-6 and IL-1 levels and on ex vivo IL-1 and IL-6 production by blood mononuclear cells.…”
Section: Cancermentioning
confidence: 99%